Genome-wide identification and expression analysis of WNK kinase gene family in rice. (December 2015) - Manuka, Rakesh; Saddhe, Ankush Ashok; Kumar, Kundan
Graphical abstract: Highlights: Identified 9 members of WNK in rice, that showed resemblance to Arabidopsis and human WNK. Phylogenetic analysis of all WNK was performed and categorized into five main clades and subclades. Their gene expression pattern of tissue specific and under various abiotic stresses reveals differential expression pattern. The presences of various abiotic stress responsive cis -elements in the promoter region of OsWNK also predict their importance in providing basal tolerance to rice during critical conditions. Abstract: Eukaryotic protein kinases represent one of the largest gene families involved in diverse regulatory functions. WNK (With No Lysine) kinases are members of ser/thr protein kinase family, which lack conserved catalytic lysine (K) residue at protein kinase subdomain II and is replaced by either asparagine, serine or glycine residues. They are involved in regulation of flowering time, circadian rhythms and abiotic stresses in Arabidopsis thaliana . In the present study, we have identified 9 members of WNK in rice, showed resemblance to Arabidopsis and human WNK and clustered into five main clades phylogenetically. The predicted genes structure, bonafide conserved signature motif and domains strongly support their identity, as members of WNK kinase family. We have analyzed their chromosomal distribution, physio-chemical properties, subcellular localizations and cis -elements in the promoter regions in silico . Further, transcript analysis of OsWNK by qRT-PCR revealed their differential regulation in tissue specific and abiotic stresses libraries. In conclusion, the identification of nine OsWNK and transcript level expression pattern under abiotic stress using qRT-PCR in rice will significantly contribute towards the understanding of WNK genes in monocots and thus provide a set up for functional genomics studies of WNK protein kinases.